PENYELESAIAN WANPRESTASI DALAM PERJANJIAN SEWA MENYEWA MOBIL BUS ANTARA PERSEROAN TERBATAS (PT) PROMITS DENGAN COMANDITAIRE VENOOTSCHAP (CV) NILAM SARI ELECTRIK DI KOTA JAMBI - Nurfauzia Nurfauzia (Wajah Hukum, 2018)
Tort started from a situation where there are parties who feel aggrieved by the other party. The execution of the lease agreement rent certainly there is conflict in its implementation, and feelings are not satisfied will appear in case of conflict. Parties who feel aggrieved will convey his discontent. In an effort to reach a solution of the problem wanpresasi is done with a variety of efforts including using litigation and non-litigation.Keywords: Tort, The Tenancy Agreement.